2012
DOI: 10.1139/x2012-005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest management legacies on spruce budworm (Choristoneura fumiferana) outbreaks

Abstract: The “silvicultural hypothesis” of spruce budworm ( Choristoneura fumiferana Clem.) dynamics postulates that increasing severity of spruce budworm outbreaks over the last century resulted from forest conditions created by past management activities. Yet, definitive tests of the hypothesis remain elusive. We examined spruce budworm outbreak dynamics (synchrony, periodicity, and intensity) in the 20th century using historical reconstruction from tree-ring chronologies sampled within 19 sites in a large ecoregion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…Future studies that compare trends from the present study with those in more northerly Canadian populations may be able to determine whether climate change is directly contributing to trends in avian abundance. Similarly, the severity and periodicity of spruce budworm (Choristoneura fumiferana) outbreaks differs considerably between the Midwestern and Eastern regions (Fraver et al, 2007;Robert et al, 2012), providing an opportunity to determine how this disturbance agent might be impacting long-term trends in associated bird species. Further investigations to identify point-level environmental and disturbance factors driving trends and how climate change affects those factors are currently under way.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies that compare trends from the present study with those in more northerly Canadian populations may be able to determine whether climate change is directly contributing to trends in avian abundance. Similarly, the severity and periodicity of spruce budworm (Choristoneura fumiferana) outbreaks differs considerably between the Midwestern and Eastern regions (Fraver et al, 2007;Robert et al, 2012), providing an opportunity to determine how this disturbance agent might be impacting long-term trends in associated bird species. Further investigations to identify point-level environmental and disturbance factors driving trends and how climate change affects those factors are currently under way.…”
Section: Discussionmentioning
confidence: 99%
“…For example, forest type bias was not evident in 2000 when wilderness disturbance was dominated by a relatively indiscriminant blow down disturbance event (Frelich, 2002). By contrast, disturbances were biased toward conifer types in 1990 and 1995, corresponding with a peak in budworm defoliation (Robert et al, 2012) and large wildfires (Fig. 3), respectively.…”
Section: Disturbance Regimesmentioning
confidence: 99%
“…Yet there is also increasing recognition that more persistent early successional stages and greater range of variability in recovery time observed following many natural disturbances can play an important role in the regional biodiversity of predominantly forested areas (Swanson et al, 2011). In addition, Robert et al (2012) found the legacy of land management in this region influences spatiotemporal dynamics of insect outbreaks, suggesting repercussions for sustainable forestry and regional forest health. Our approach can therefore help inform land managers who must balance a diversity of objectives and values over time and space.…”
Section: Management Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Volume 398 reduction was least under the increased spruce objective, assuming black spruce, at 20% by the 399 end of the outbreak simulation (Fig. However, our 434 results may not entirely address this question, as host connectivity or forest contiguity, which 435 were not accounted for in our model, could play a role in determining the damage generated by 436 SBW at the landscape scale (Robert et al 2012). 9b).In comparison, volume reductions for unmanaged stands, increased mixedwood and 401 balanced composition objectives were 43-44% assuming that spruce was black, versus 50-53% 402 assuming that spruce was white.…”
mentioning
confidence: 84%